ChemInform Abstract: Regioselective ortho‐Carboxylation of Phenols Catalyzed by Benzoic Acid Decarboxylases: A Biocatalytic Equivalent to the Kolbe—Schmitt Reaction. Issue 38 (10th September 2014) - Wuensch, Christiane; Gross, Johannes; Steinkellner, Georg; Lyskowski, Andrzej; Gruber, Karl; Glueck, Silvia M.; Faber, Kurt
Abstract Several decarboxylases are tested for exclusively selective ortho‐carboxylation of phenols under ambient reaction conditions using bicarbonate as CO2 source.